Integrasi Nilai Green-Constitution Melalui pendekatan Deep Learning dalam Pembentukan Karakter Peduli Lingkungan - Sunarto Amus; Sukmawati sukmawati; Jamaludin Jamaludin; Rahmawati Rahmawati; Reza Oktaviani Maindo; Hardian Ningsi Safitri (Universitas PGRI Kanjuruhan Malang, 2025)
The growing complexity of environmental crises demands that education plays a strategic role in fostering ecological awareness and environmentally responsible character among younger generations. One relevant approach is the integration of Green-Constitution values— a set of principles emphasizing that environmental preservation is part of human rights, a collective responsibility of citizens, and a constitutional obligation of the state. These values include the right to a clean and healthy environment, active participation in environmental governance, ecological justice, and intergenerational sustainability. This study aims to analyze the effectiveness of a learning approach that integrates Green-Constitution values with Deep Learning strategies in shaping environmental awareness and responsibility among students at SMAN Model Terpadu Madani Palu. The methodology involved pre-test and post-test assessments of 101 respondents, complemented by qualitative descriptive analysis of student responses. Initial findings revealed that students had a basic understanding of the right to a healthy environment, yet lacked a comprehensive connection to constitutional aspects and sustainable development goals. Following the implementation of value-based and reflective learning, there was a significant improvement in conceptual understanding, critical ecological awareness, and pro-environmental attitudes. These were manifested in real behavioral changes such as bringing reusable water bottles, sorting waste, planting trees, and conserving energy at school. The findings indicate that the integration of Green-Constitution values and Deep Learning is effective in systematically and contextually cultivating students’ ecological character.